2013
DOI: 10.5901/jesr.2013.v3n7p317
|View full text |Cite
|
Sign up to set email alerts
|

An Action Research on Developing Prospective Teachers’ Inquiry Skills

Abstract: One of the ultimate aims of teacher education programs is to equip prospective teachers with the necessary professional skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Many studies in the field of science education and science teachers' 3Ps (that is, PSSTs' 3Ps) revealed that there is a misunderstanding on knowledge and skills of scientific research mainly SRHs. Though the issue of preparing teacher as a researcher has been globally considered and studied by several researchers in diverse educational researches for different purposes (Kuter, 2013;Özdilek and Bulunuz, 2009;Tuberty et al, 2011;Darus and Saat, 2014;Ural, 2016), it was hardly studied in the context of Yemeni PSSTs' 3Ps at Faculty of Education in Amran University.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies in the field of science education and science teachers' 3Ps (that is, PSSTs' 3Ps) revealed that there is a misunderstanding on knowledge and skills of scientific research mainly SRHs. Though the issue of preparing teacher as a researcher has been globally considered and studied by several researchers in diverse educational researches for different purposes (Kuter, 2013;Özdilek and Bulunuz, 2009;Tuberty et al, 2011;Darus and Saat, 2014;Ural, 2016), it was hardly studied in the context of Yemeni PSSTs' 3Ps at Faculty of Education in Amran University.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another means for student teachers' involvement in inquiry is through collaboration (Kuter, 2013). Engagement of student teachers in a collaborative classroom inquiry to develop handwriting skills of children helped them develop their reflection and inquiry skills (Medwell & Wray, 2014).…”
Section: Research Studiesmentioning
confidence: 99%
“…One of the ultimate aims of teacher education programs is to equip prospective teachers with the necessary professional skills and dispositions so that they can build and maintain a philosophy of teaching and learning that is constantly reviewed based on an understanding of research and practices. Developing student teachers' inquiry skills by engaging them in research is one of the indispensable parts of teacher education programs since it provides the basis of their ongoing professional development (S. Kuter [4]). S. K. DebBurman suggests that the involvement of students in real research projects promotes interest and learning in complex scientific content, helps develop science experimental skills and enables students to gain familiarity with the science culture (S. K. DebBurman [5]).…”
Section: Introductionmentioning
confidence: 99%
“…It must be emphasized that this problem is also relevant for Kazakhstani higher education. Of particular relevance is also the issue of modernizing the educational space of the Kazakhstani higher school 4 In psychological and pedagogical science, prerequisites have been created for studying the formation of special competencies of future primary school teachers on the basis of the project method in the process of vocational training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation